The Current Role of Osteoclast Inhibitors in Patients with Prostate Cancer - Diomidis Kozyrakis; Dionyssios Paridis; Stefanos Perikleous; Konstantinos Malizos; Anastasios Zarkadas; Antonios Tsagkalis (Advances in Urology)
Purpose. Prostate cancer (PCa) is one of the most frequently diagnosed malignancies worldwide. Hormonal deprivation therapy is a well-established treatment for locally advanced or metastatic diseases but exposes patients to the risk of osteoporosis and fragility fractures. Furthermore, the tropism of the PCa cells to osseous metastases increases the incidence of skeletal-related events (SREs). Methods. A nonsystematic review of the international literature was performed in respect to the use of osteoclast inhibitors zoledronic acid (ZA) and denosumab (DEN) in PCa patients. Results. DEN and ZA have proved their efficacy in preventing osteoporosis and bone mass loss in patients treated with hormonal therapy with no proven superiority of one agent over the other. However, the effectiveness in reducing fragility fractures has been proved only for DEN so far. In metastatic-free castrate-sensitive high-risk PCa patients, ZA has not shown any efficacy in preventing osseous metastasis, and evidence is lacking in favor or against the use of DEN. The use of osteoclasts inhibitors had no evident positive effect in overall and disease-specific survival in this group of patients. In advanced castrate-refractory malignancy, DEN has shown clinical superiority over ZA in preventing new SRE but not in overall survival. Conclusion. Superiority of DEN over ZA has been proved only in advanced castrate refractory disease in terms of preventing new SRE. In the rest of the cases, the selection of either agent should be based on the clinical condition of each patient and the cost of the treatment.